2013
DOI: 10.1523/jneurosci.5193-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the Rules: Distinct and Overlapping Frontoparietal Representations of Task Rules for Perceptual Decisions

Abstract: Behavior is governed by rules that associate stimuli with responses and outcomes. Human and monkey studies have shown that rulespecific information is widely represented in the frontoparietal cortex. However, it is not known how establishing a rule under different contexts affects its neural representation. Here, we use event-related functional MRI (fMRI) and multivoxel pattern classification methods to investigate the human brain's mechanisms of establishing and maintaining rules for multiple perceptual decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 60 publications
3
96
1
Order By: Relevance
“…For example, we previously reported that discrimination between two stimulusresponse mapping rules in the visual cortex generalizes over the two visual stimuli used to cue each rule . Similarly, Zhang et al (2013) found that rule discrimination in the calcarine sulcus generalized over externally cued and internally chosen rules, and Soon, Namburi, and Chee (2013) reported rule discrimination in the visual cortex when rules were cued with an auditory cue. In some cases, rule discrimination in the visual cortex may reflect different preparatory signals, for example, if the two rules direct attention to different visual features (e.g., Zhang et al, 2013) or object categories (e.g., Soon et al, 2013), but this is not always the case: the two rules of required attention to the same features of identical visual stimuli.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, we previously reported that discrimination between two stimulusresponse mapping rules in the visual cortex generalizes over the two visual stimuli used to cue each rule . Similarly, Zhang et al (2013) found that rule discrimination in the calcarine sulcus generalized over externally cued and internally chosen rules, and Soon, Namburi, and Chee (2013) reported rule discrimination in the visual cortex when rules were cued with an auditory cue. In some cases, rule discrimination in the visual cortex may reflect different preparatory signals, for example, if the two rules direct attention to different visual features (e.g., Zhang et al, 2013) or object categories (e.g., Soon et al, 2013), but this is not always the case: the two rules of required attention to the same features of identical visual stimuli.…”
Section: Discussionmentioning
confidence: 87%
“…Analyses pertaining to the discrimination of task rules included discrimination of different stimulus-response mappings (e.g., Bode & Haynes, 2009), intended tasks (e.g., addition vs. subtraction; Haynes et al, 2007) and task set (e.g., attend to motion vs. color vs. size; Zhang, Kriegeskorte, Carlin, & Rowe, 2013). Two analyses were included in our lenient categorization and excluded from the strict categorization.…”
Section: Characterization Of Task Featuresmentioning
confidence: 99%
“…5). However, other studies have also linked SMA activity to voluntary action selection (Lau et al, 2004;Zhang et al, 2012Zhang et al, , 2013 or selfinitiated movements (Cunnington et al, 2002(Cunnington et al, , 2003Fried et al, 2011). Further work will be required to define the specific role of the SMA and preSMA, and possibly also posterior parietal and premotor regions, in stimulus-response mapping and movement planning.…”
Section: Areas Involved In Stimulus-response Associationsmentioning
confidence: 99%
“…Across two experiments, we scanned subjects with high-resolution fMRI while they performed tasks that demanded selective integration of noisy sensory evidence according to a shifting decision rule, or context. During rule-based decision-making, distributed patterns of activation in lateral PFC encode a representation of task context (21)(22)(23). We have previously reported that these context representations are strongly expressed in the inferior frontal sulcus (IFS), a prefrontal region defined through large-scale analyses of spontaneous correlations (24,25).…”
mentioning
confidence: 99%